Patterns and Causes of Long Bone Fractures in Dogs: A Two-Year Retrospective Study - Palli, Ravi Kumar; Vaddadi, Devi Prasad; Rao, Mallikarjuna; Devarakonda, Srikala (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
A retrospective study was conducted on 173 dogs with long bone fractures among 9,784 dogs presented to SVVU Super Speciality Veterinary Hospital, Visakhapatnam, from January 2022 to December 2023. Males and juvenile dogs were most frequently affected. Mongrels and small breeds such as Spitz and Pomeranians showed higher susceptibility. Hind limbs were slightly more involved than forelimbs, with radius-ulna and femur being the most commonly fractured bones. Falls from height and vehicular accidents were the major causes. Keywords: Canine, Epidemiology, Hind limb, Long bone fracture, Trauma.